Analisis Kepuasan Pelanggan Terhadap Aplikasi Pelayanan Pelanggan dengan Metode CSI dan ServQual - Andreas Adi Trinoto; Ahmad Zamakhsari (Universitas Indraprasta PGRI Jakarta, 2021)
Kereta Api Indonesia (KAI) as one of the state-owned companies that provide services to the public feels good a few years back and is the aim of researchers to conduct a survey of customer satisfaction with one of the Microsoft product Genesys customer service applications that have been connected with social media as a supporting application in serving train service users. The method used by researchers is the CSI (Customer Satisfaction Index) and Service Quality, the Jakarta Central Railway office agent who filled in the questionnaires as much as 51 of 80 with 78.76% results in CSI and 0.24 on servqual. This customer service application has a positive effect on customer satisfaction, as well as an evaluation for application providers.